They do not deserve your thanks! Witness reactions to leader-directed expressions of gratitude. - Fehr, Ryan; Heng, Yu Tse; Wang, Yue; Guo, Yirong (Journal of Applied Psychology, 2025)
Gratitude expressions have received growing attention from scholars, with research emphasizing its many positive effects on expressers, recipients, and witnesses. Although our knowledge of gratitude expressions' benefits is accumulating, our understanding of its limits is less developed. In this article, we ask when employees' expressions of gratitude toward their leaders positively influence witnesses' perceptions of them, and when they do not. Across three studies including two multiwave surveys and an experiment, we find that expressed gratitude strengthens witnesses' perceptions of expressers' prosocial identities, especially when the leader is believed to be deserving of gratitude. Study 1 examines leader competence as an indicator of deservingness in a sample of leaders and employees in a manufacturing context. Studies 2 and 3 use survey and experimental methods to directly establish leader deservingness as a mechanism of the competence moderator and explore warmth as an additional component of employees' deservingness perceptions. All three studies show how gratitude expression ultimately shapes witnesses' tendencies to help expressers and seek feedback from them. (PsycInfo Database Record (c) 2025 APA, all rights reserved).